2022
DOI: 10.1111/kykl.12294
|View full text |Cite
|
Sign up to set email alerts
|

How gender, marital status, and gender norms affect savings goals

Abstract: Setting savings goals can increase wealth accumulation behaviour, yet it depends on how challenging the goals are. Using rarely available savings goal data from 1,760 clients of an advisory investment firm, we identify gender attitudinal differences in goal amounts: men choose more ambitious savings goals than women, independently from expected life‐long earnings. This, however, holds only for individuals living in a couple, for which men's savings goals reach the highest levels. Based on insights from qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…This behavior, while deviating from those expected of rational investors, should not be understood as irrational (bounded rationality [Strauss, 2008]) or not suitable for the complexity of the environment (environment-consistent rationality [Lavoie, 2015]) but are developed as a response to the normative context of social reproduction generally, and workplace pensions specifically. Interviewees find the inherent constraints in pensions as reasons for disengaging from them, especially since their responsibility for childcare, domestic chores and day-to-day budgeting leads to a desire for more accessible savings (Agunsoye et al, 2022). Gender-normative roles of the non-financial person (Enloe, 2013;Sent & van Staveren, 2019) are employed to justify the disengagement from pensions as it appears to take substantial effort to inform themselves about pensions which are not accessible when needed and where its in-built structural constraints would cause a disruption to pension savings when having children.…”
Section: Discussion: Gendered Finance Rationalitymentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior, while deviating from those expected of rational investors, should not be understood as irrational (bounded rationality [Strauss, 2008]) or not suitable for the complexity of the environment (environment-consistent rationality [Lavoie, 2015]) but are developed as a response to the normative context of social reproduction generally, and workplace pensions specifically. Interviewees find the inherent constraints in pensions as reasons for disengaging from them, especially since their responsibility for childcare, domestic chores and day-to-day budgeting leads to a desire for more accessible savings (Agunsoye et al, 2022). Gender-normative roles of the non-financial person (Enloe, 2013;Sent & van Staveren, 2019) are employed to justify the disengagement from pensions as it appears to take substantial effort to inform themselves about pensions which are not accessible when needed and where its in-built structural constraints would cause a disruption to pension savings when having children.…”
Section: Discussion: Gendered Finance Rationalitymentioning
confidence: 99%
“…Because of expecting the occurrence of adverse events ('it's always worrying that I might need money' [Rita, low income]) emanating from gender-normative roles of being responsible for childcare, daily chores such as grocery shopping and dayto-day budgeting within the household (Agunsoye et al, 2022;D'Acunto et al, 2020), women want to be able to access money they have saved: 'I like to know where my money is and that I can get a hold of it when I need to get a hold of it' (Claudia, low income). The desire to remain flexible in case of short-term financial needs ('I didn't want anything, I couldn't access' [Layla, lower medium income]) stands in contrast to the lack of accessibility and flexibility inherent in workplace pensions.…”
Section: Employing the Normative Context To Disengagementioning
confidence: 99%
“…Lee and Hanna (2015) mapped the top saving goals listed by the survey of consumer finance (SCF) to the different levels of Maslow's hierarchy of needs and found that goals related to the human need for self-actualization and retirement/security had the strongest associations with savings behavior. Finally, prior literature has shown that savings goals do reflect subsequent savings behaviors (Agunsoye et al, 2022). Rohan (2000) acknowledged that defining "values" in academic research is difficult given that the word can be used in many different ways, both as a verb and a noun.…”
Section: Measurement Of Life Goalsmentioning
confidence: 99%
“…Most women are responsible for daily budget management, which exacerbates concerns about financial stability in the short term and has a detrimental influence on savings goals. It is found true even when women, rather than males, control the household's long-term investments [31]. As women are becoming more affluent in their financial decisionmaking, the need for personal finance planning increases.…”
Section: Personal Financial Planningmentioning
confidence: 99%